Multifunctional CuBiS2 Nanoparticles for Computed Tomography Guided Photothermal Therapy in Preventing Arterial Restenosis After Endovascular Treatment - Wu, Xiaoyu; Liu, Kun; Wang, Ruihua; Yang, Guanglin; Lin, Jiaying; Liu, Xiaobing (Frontiers in Bioengineering and Biotechnology, 2020)
Chronic inflammation mediated by artery infiltrated macrophages plays critical role in artery restenosis after endovascular therapy. Evidence has demonstrated the potential ability of photothermal therapy (PTT) in eliminating chronic inflammation by targeting inflammatory cells including macrophages. Recently, increasing attention has been payed to copper chalcogenide nanocrystals doped of radiocontrast agent e.g. bismuth (Bi) for computed tomography (CT) guided PTT. However, the application of imaging guided PTT in preventing artery restenosis is lacking and limited. Herein, a novel multifunctional CuBiS2 nanoparticles (CuBiS2 NPs) were synthesized for CT imaging guided PTT in artery re-stenosis prevention. The optimum amount and other conditions of CuBiS2 NPs were optimized to exert the maximum ablation effect on macrophages with good biocompatibility. In vivo carotid injury model revealed that CuBiS2 NPs exhibited promising therapeutic effect on inhibition of artery stenosis by eliminating macrophages with excellent CT imaging ability. The recent study highlights a new cost-effective metal nanostructures-based nanotechnology in prevention of artery restenosis after endovascular therapy.